2020
DOI: 10.1038/s41586-020-2180-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the SARS-CoV-2 spike receptor-binding domain bound to the ACE2 receptor

Abstract: A new and highly pathogenic coronavirus (severe acute respiratory syndrome coronavirus-2, SARS-CoV-2) caused an outbreak in Wuhan city, Hubei province, China, starting from December 2019 that quickly spread nationwide and to other countries around the world 1-3 . Here, to better understand the initial step of infection at an atomic level, we determined the crystal structure of the receptor-binding domain (RBD) of the spike protein of SARS-CoV-2 bound to the cell receptor ACE2. The overall ACE2-binding mode of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

247
7,370
13
69

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 5,768 publications
(7,699 citation statements)
references
References 30 publications
247
7,370
13
69
Order By: Relevance
“…Interestingly, we observed in our models that the RBD is predicted to pack similarly to SARS-CoV and the RBM is also predicted to organize as a flexible loop with similar structure despite the lower amino acid identity between these two proteins ( Figure 6). In a more recent report, it has been shown that ACE2-binding mode of both SARS-CoV and SARS-CoV-2 RBDs is nearly identical, which supports the claim that the flexibility in the RBM is key to compensate the amino acid differences between the two CoVs proteins and agrees with our predicted models [54].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, we observed in our models that the RBD is predicted to pack similarly to SARS-CoV and the RBM is also predicted to organize as a flexible loop with similar structure despite the lower amino acid identity between these two proteins ( Figure 6). In a more recent report, it has been shown that ACE2-binding mode of both SARS-CoV and SARS-CoV-2 RBDs is nearly identical, which supports the claim that the flexibility in the RBM is key to compensate the amino acid differences between the two CoVs proteins and agrees with our predicted models [54].…”
Section: Discussionsupporting
confidence: 90%
“…During the preparation of this manuscript, the cryo-electron microscopy structures of SARS-CoV-2 S have recently been determined [33,52,53]. These studies have revealed in detail the structure of the SARS-CoV-2 spike RBD and how it contacts the ACE2 host cell receptor with notable differences compared to SARS-CoV [54]. It has been described that the SARS-CoV RBM "down" conformation packs more closely to the NTD of the S protein [33].…”
Section: Discussionmentioning
confidence: 99%
“…The angiotensin I converting enzyme 2 (ACE2) serves as a functional receptor for the spike protein (S) of SARS-CoV and SARS-CoV-2 (12,13) . Under normal physiological conditions, ACE2 is a dipeptidyl carboxypeptidase that catalyzes the conversion of angiotensin I into angiotensin 1-9, a peptide of unknown function, and angiotensin II, a vasoconstrictor that is important in the regulation of blood pressure (14) .…”
Section: Introductionmentioning
confidence: 99%
“…The host range of SARS-CoV-2 may be extremely broad due to the conservation of ACE2 in mammals (2,13) and its expression on ciliated bronchial epithelial cells and type II pneumocytes (10) . While coronaviruses related to SARS-CoV-2 use ACE2 as a primary receptor, coronaviruses may use other proteases as receptors, such as CD26 (DPP4) for MERS-CoV (16) , thus limiting or extending their host range.…”
Section: Introductionmentioning
confidence: 99%
“…We use the structure of the SARS-CoV-2 spike receptor-binding domain bound with ACE2 (PDB code 6m0j) 9 and SARS-CoV-2 spike receptor-binding domain bound to full length ACE2 (PDB code 6m17) 4 . The two protein complexes, 6m0j and 6m17, were used in the case of the interface mediating the interaction between the spike protein (S-prot) and ACE2 while the latter was use to model and design peptides to target the interface between ACE2 monomers ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%